Adhesive for electromagnetic degumming of photovoltaic cutting base plate and preparation method of adhesive
By optimizing the component ratio and process processing in the adhesive formula, the problem of difficulty in degumming the existing adhesive under electromagnetic degumming method is solved, and the effect of rapid degumming and no residual glue is achieved, which improves production efficiency and reduces costs.
Patent Information
- Application Number
- CN202411745750.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-11
AI Technical Summary
The existing adhesive cannot be degummed quickly under electromagnetic degumming, which makes it difficult to remove the cutting pad and the residual glue on the workpiece plate.
A new adhesive formula is adopted, including component A and component B. Component A contains epoxy resin, diluent, dispersant, defoaming agent, filler, foaming agent and pigment. Component B contains curing agent, epoxy promoter, diluent, filler, foaming promoter and anti-deposition agent. Through specific component ratios and process treatment, the curing hardness and bonding strength of the adhesive are improved, and the reaction of the foaming agent can be achieved quickly during the electromagnetic degumming process.
It realizes rapid degumming under electromagnetic degumming method, and the cutting pad can be quickly removed, and the workpiece plate has no residual glue residue, which improves the turnover rate of the workpiece plate and reduces production costs.
Smart Images

Figure BDA0005163679910000141 
Figure BDA0005163679910000151
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesives, and in particular to an adhesive used for electromagnetic debonding of photovoltaic cutting pads and a preparation method thereof. Background Art
[0002] In the photovoltaic slicing manufacturing process, after the silicon wafer is cut, the adhesive-bonded pad needs to be removed from the workpiece plate and the workpiece plate needs to be recycled. In the past, this degumming step usually relied on a time-consuming, energy-intensive and costly high-temperature water boiling method. However, in view of the current growing demand for cost reduction and efficiency improvement, as well as the rapid development of automated production, the degumming process has shifted from traditional manual high-temperature water boiling to a more efficient automated electromagnetic degumming method, which has significantly improved production capacity and work efficiency. However, the change in degumming method has posed new challenges to the adhesives used for bonding pads. Conventional adhesives that were previously suitable for high-temperature water boiling degumming have problems with degumming, the inability to remove the cutting pads, and the difficulty in handling residual adhesive on the workpiece plate when faced with the new electromagnetic degumming process.
[0003] Chinese patent CN114605954A discloses a two-component polyurethane adhesive with high adhesion and quick debonding by boiling in water. Compared with epoxy system adhesives, polyurethane system is easier to debond by boiling in water at 90-100℃; Chinese patent CN115353847B discloses a two-component anti-cracking seam beautifying agent and its preparation method, which can debond quickly in a boiling environment, improve production efficiency, save energy, and can significantly improve the efficiency of adhesive removal when used as an adhesive for photovoltaic cutting. However, the adhesives in the above technologies are all debonded by high-temperature boiling debonding, and still cannot be debonded quickly under the electromagnetic debonding method.
[0004] Therefore, an adhesive solution is needed that can match the automatic line bonding electromagnetic debonding method, meet the requirements of rapid debonding of the pad, and have no residual adhesive on the workpiece plate after debonding. Summary of the invention
[0005] In order to solve the problems in the prior art, the first aspect of the present invention provides an adhesive for electromagnetic debonding of photovoltaic cutting pads, and the raw materials for preparing the adhesive include:
[0006] Component A: by weight, including 40-70 parts of epoxy resin, 2-6 parts of first diluent, 0.1-0.5 parts of dispersant, 0.1-0.5 parts of defoamer, 20-40 parts of first filler, 1-4 parts of foaming agent, 1-3 parts of first pigment, and 0.1-0.8 parts of first anti-settling agent;
[0007] Component B: by weight, including 40-75 parts of curing agent, 1-5 parts of epoxy accelerator, 1-5 parts of second diluent, 0.1-0.3 parts of second pigment, 20-50 parts of second filler, 10-20 parts of foaming accelerator, and 0.1-0.3 parts of second anti-settling agent.
[0008] In one embodiment, the mass ratio of component A to component B is 1:1.
[0009] In one embodiment, the epoxy resin is selected from at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, and novolac epoxy resin.
[0010] In a preferred embodiment, the epoxy resin is selected from any two of bisphenol A epoxy resin, bisphenol F epoxy resin, and novolac epoxy resin.
[0011] In a preferred embodiment, the bisphenol A epoxy resin is selected from at least one of bisphenol A epoxy resin E51 and bisphenol A epoxy resin E44.
[0012] In a preferred embodiment, the bisphenol A epoxy resin E51 and bisphenol A epoxy resin E44 are both purchased from Nanya Electronic Materials (Kunshan) Co., Ltd.
[0013] In a preferred embodiment, the bisphenol F epoxy resin includes bisphenol F epoxy resin 170, and the bisphenol F epoxy resin 170 is purchased from Nanya Electronic Materials (Kunshan) Co., Ltd.
[0014] In a preferred embodiment, the novolac epoxy resin includes modified novolac epoxy resin F44, and the modified novolac epoxy resin F44 is purchased from Nanya Electronic Materials (Kunshan) Co., Ltd.
[0015] In one embodiment, the first diluent and the second diluent are both selected from at least one of benzyl alcohol, allyl alcohol glycidyl ether, N-methyl pyrrolidone, diethylene glycol butyl ether, tert-butyl ether, and butyl phthalate.
[0016] In one embodiment, the first diluent is allyl alcohol glycidyl ether.
[0017] In a preferred embodiment, the allyl alcohol glycidyl ether is purchased from Shanghai Kaiyin Chemical Co., Ltd.
[0018] In one embodiment, the second diluent is benzyl alcohol.
[0019] In a preferred embodiment, the benzyl alcohol is purchased from Shanghai Kaiyin Chemical Co., Ltd.
[0020] In one embodiment, the dispersant is purchased from BYK Chemical of Germany, and the brand is selected from at least one of BYK106, BYK140, and BYK108.
[0021] In one embodiment, the defoaming agent is purchased from BYK Chemicals of Germany, and the brand is selected from at least one of BYK016 and BYK024.
[0022] In one embodiment, the first filler and the second filler are both selected from at least one of calcium carbonate, aluminum powder, magnesium hydroxide, barium sulfate, and calcium hydroxide.
[0023] In a preferred embodiment, the calcium carbonate has a mesh size of 1250 and is purchased from Dexing Longsheng Calcium Carbonate Co., Ltd.
[0024] In a preferred embodiment, the aluminum powder has a mesh size of 2000 mesh and is purchased from Changyuan County Mingyu Aluminum Co., Ltd.
[0025] In a preferred embodiment, the mesh size of the magnesium hydroxide is 2000 mesh and is purchased from Weifang Haililong Magnesium Co., Ltd.
[0026] In a preferred embodiment, the barium sulfate has a mesh size of 6000 mesh and is purchased from Langfang Yinma Pigment Co., Ltd.
[0027] In a preferred embodiment, the calcium hydroxide has a mesh size of 2000 mesh and is purchased from Jiangxi Chuangxian Fine Calcium Industry Co., Ltd.
[0028] In one embodiment, the foaming agent is selected from at least one of a sulfonylhydrazide foaming agent and an amide foaming agent.
[0029] In one embodiment, the sulfonylhydrazide foaming agent includes at least 4,4'-oxybisbenzenesulfonylhydrazide.
[0030] In a preferred embodiment, the 4,4'-oxybisbenzenesulfonyl hydrazide is purchased from Guangdong Duba New Materials Co., Ltd.
[0031] In one embodiment, the amide foaming agent includes at least azodicarbonamide.
[0032] In a preferred embodiment, the azodicarbonamide is purchased from Guangdong Duba New Materials Co., Ltd.
[0033] In one embodiment, the epoxy accelerator is a phenolic epoxy accelerator.
[0034] In a preferred embodiment, the phenolic epoxy accelerator is purchased from Shanghai Qiguang Industry and Trade Co., Ltd. with a brand name of DMP-30.
[0035] In one embodiment, the pigment is selected from at least one of titanium dioxide and carbon black.
[0036] In a preferred embodiment, the titanium dioxide has a mesh size of 2000 mesh and is purchased from Longbai Group Co., Ltd.
[0037] In one embodiment, the first anti-settling agent and the second anti-settling agent both include fumed silica.
[0038] In a preferred embodiment, the fumed silica is purchased from Hubei Huifu Nanomaterials Co., Ltd.
[0039] In one embodiment, the curing agent is selected from at least one of a modified polythiol curing agent and a modified amine epoxy curing agent.
[0040] In a preferred embodiment, the curing agent includes a modified polythiol curing agent and a modified amine epoxy curing agent.
[0041] In one embodiment, the mass ratio of the modified polythiol curing agent to the modified amine epoxy curing agent is 33-41:13-18.
[0042] In a preferred embodiment, the mass ratio of the modified polythiol curing agent to the modified amine epoxy curing agent is any one of 33:18, 38:16, and 41:13.
[0043] In one embodiment, the viscosity of the modified polythiol curing agent at 25° C. is 10,000-15,000 MPa·s.
[0044] In a preferred embodiment, the modified polythiol curing agent is purchased from Guangzhou Green New Materials Co., Ltd. and the brand is polythiol 309.
[0045] In one embodiment, the modified amine epoxy curing agent is a diethylenetriamine modified amine epoxy curing agent, the viscosity of the modified amine epoxy curing agent at 25° C. is 10000-20000 MPa·s, and the amine value is 200-500 mg KOH / g.
[0046] In a preferred embodiment, the modified amine epoxy curing agent has a viscosity of 10000-20000 MPa·s at 25° C. and an amine value of 300-350 mg KOH / g.
[0047] In a more preferred embodiment, the modified amine epoxy curing agent has a viscosity of 10,000-20,000 MPa·s at 25° C. and an amine value of 315 mg KOH / g.
[0048] In a more preferred embodiment, the modified amine epoxy curing agent is purchased from Rich Chemical (Hubei) Co., Ltd. with a brand name of R-2028.
[0049] In one embodiment, the foaming promoter is selected from at least one of urea and zinc stearate.
[0050] In a preferred embodiment, the urea and zinc stearate are both purchased from Jinan Qicai Chemical Co., Ltd.
[0051] In one embodiment, the pigment filler is an organic color paste.
[0052] In a preferred embodiment, the organic color paste is purchased from Guangzhou Panyu Kedi Color Co., Ltd. with a brand number of 4254.
[0053] The second aspect of the present invention provides a method for preparing an adhesive for electromagnetic debonding of photovoltaic cutting pads, which comprises at least the following steps: mixing component A and component B respectively and stirring them according to a mass ratio.
[0054] Beneficial Effects
[0055] 1. Based on the present application system, the curing hardness and bonding strength of the adhesive used for electromagnetic debonding of photovoltaic cutting pads are improved by optimizing the selection of epoxy resin.
[0056] 2. Based on the system of this application, by controlling the viscosity and amine value of the curing agent, the electromagnetic debonding time and shear strength of the adhesive used for electromagnetic debonding of photovoltaic cutting pads can be balanced.
[0057] 3. The present application adopts specific foaming agents and foaming promoters. During the electromagnetic debonding process, the electromagnetic equipment heats the workpiece plate, causing the glue layer to be heated. The foaming agent in the glue layer reacts under the heating conditions and decomposes into gas, causing the glue layer to fall off first on the side in contact with the iron plate, and finally separating the cutting pad from the workpiece plate. This process only takes about 60 seconds, and no glue film remains on the workpiece plate, and no human intervention is required.
[0058] 4. The adhesive for electromagnetic debonding of photovoltaic cutting pads provided in this application can meet the client's needs for automated electromagnetic debonding. Under the electromagnetic debonding method, the cutting pads can be quickly debonded, and no residual glue will remain on the workpiece plate, thereby improving the turnover rate of the workpiece plate, greatly improving the company's production capacity, and saving unnecessary production costs.
[0059] 5. The preparation method of the adhesive for electromagnetic debonding of photovoltaic cutting pads provided in this application has a simple preparation process and can reduce production costs. DETAILED DESCRIPTION
[0060] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. The experimental methods in the examples without specifying specific conditions are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without specifying the manufacturer are all conventional products that can be purchased commercially.
[0061] Example 1
[0062] In a first aspect of the present embodiment, there is provided an adhesive for electromagnetic debonding of a photovoltaic cutting pad, wherein the raw materials for preparing the adhesive include:
[0063] Component A: by weight, including 30 parts of bisphenol A epoxy resin E51, 32 parts of bisphenol A epoxy resin E44, 4 parts of a first diluent, 0.1 parts of a dispersant, 0.1 parts of a defoamer, 28.2 parts of a first filler, 4 parts of a foaming agent, 1 part of a first pigment, and 0.6 parts of a first anti-settling agent;
[0064] Component B: by weight, including 54 parts of curing agent, 5 parts of epoxy accelerator, 2 parts of second diluent, 0.3 parts of second pigment, 27.6 parts of second filler, 12 parts of foaming accelerator, and 0.1 parts of second anti-settling agent.
[0065] The mass ratio of the A component to the B component is 1:1.
[0066] The bisphenol A epoxy resin E51 and bisphenol A epoxy resin E44 were purchased from Nanya Electronic Materials (Kunshan) Co., Ltd.
[0067] The first diluent is allyl alcohol glycidyl ether, purchased from Shanghai Kaiyin Chemical Co., Ltd.
[0068] The second diluent is benzyl alcohol, purchased from Shanghai Kaiyin Chemical Co., Ltd.
[0069] The dispersant was purchased from BYK Chemicals of Germany with the brand name BYK140.
[0070] The defoamer was purchased from BYK Chemicals of Germany with the brand name BYK016.
[0071] The first filler is aluminum powder, the mesh number of the aluminum powder is 2000 mesh, and it is purchased from Changyuan County Mingyu Aluminum Co., Ltd.
[0072] The second filler is calcium carbonate, the mesh number of the calcium carbonate is 1250 mesh, and it is purchased from Dexing Longsheng Calcium Carbonate Co., Ltd.
[0073] The foaming agent is 4,4'-oxybisbenzenesulfonyl hydrazide, which is purchased from Guangdong Duba New Materials Co., Ltd.
[0074] The pigment is titanium dioxide, the mesh number of the titanium dioxide is 2000 mesh, and it is purchased from Longbai Group Co., Ltd.
[0075] The first anti-settling agent and the second anti-settling agent are both fumed silica, and the fumed silica is purchased from Hubei Huifu Nanomaterial Co., Ltd.
[0076] The curing agent is a modified polythiol curing agent and a modified amine epoxy curing agent.
[0077] The mass ratio of the modified polythiol curing agent to the modified amine epoxy curing agent is 41:13.
[0078] The modified polythiol curing agent was purchased from Guangzhou Green New Materials Co., Ltd., with the brand name of polythiol 309.
[0079] The modified amine epoxy curing agent was purchased from Rich Chemical (Hubei) Co., Ltd. with the brand name R-2028.
[0080] The epoxy accelerator is a phenol epoxy accelerator purchased from Shanghai Qiguang Industry and Trade Co., Ltd. with a brand name of DMP-30.
[0081] The foaming promoter is urea, which was purchased from Jinan Qicai Chemical Co., Ltd.
[0082] The pigment filler is an organic color paste purchased from Guangzhou Panyu Kedi Color Co., Ltd. with a brand number of 4254.
[0083] A second aspect of the present embodiment provides a method for preparing an adhesive for electromagnetic debonding of photovoltaic cutting pads, which comprises at least the following steps: mixing component A and component B respectively and stirring them according to the mass ratio.
[0084] Example 2
[0085] In a first aspect of the present embodiment, there is provided an adhesive for electromagnetic debonding of a photovoltaic cutting pad, wherein the raw materials for preparing the adhesive include:
[0086] Component A: by weight, including 50 parts of modified phenolic epoxy resin F44, 18 parts of bisphenol A epoxy resin E44, 6 parts of a first diluent, 0.1 parts of a dispersant, 0.1 parts of a defoamer, 20.2 parts of a first filler, 4 parts of a foaming agent, 1 part of a first pigment, and 0.6 parts of a first anti-settling agent;
[0087] Component B: by weight, including 54 parts of curing agent, 4 parts of epoxy accelerator, 3 parts of second diluent, 0.3 parts of second pigment, 26.4 parts of second filler, 12 parts of foaming accelerator, and 0.3 parts of second anti-settling agent.
[0088] The mass ratio of the component A to the component B is 1:1.
[0089] The bisphenol A epoxy resin E44 and modified novolac epoxy resin F44 were purchased from Nanya Electronic Materials (Kunshan) Co., Ltd.
[0090] The first diluent is allyl alcohol glycidyl ether, purchased from Shanghai Kaiyin Chemical Co., Ltd.
[0091] The second diluent is benzyl alcohol, purchased from Shanghai Kaiyin Chemical Co., Ltd.
[0092] The dispersant was purchased from BYK Chemicals of Germany with the brand name BYK140.
[0093] The defoamer was purchased from BYK Chemicals of Germany with the brand name BYK016.
[0094] The first filler is magnesium hydroxide, the mesh number of the magnesium hydroxide is 2000 mesh, and it is purchased from Weifang Haililong Magnesium Industry Co., Ltd.
[0095] The second filler is calcium carbonate, the mesh number of the calcium carbonate is 1250 mesh, and it is purchased from Dexing Longsheng Calcium Carbonate Co., Ltd.
[0096] The foaming agent is 4,4'-oxybisbenzenesulfonyl hydrazide, which is purchased from Guangdong Duba New Materials Co., Ltd.
[0097] The pigment is titanium dioxide, the mesh number of the titanium dioxide is 2000 mesh, and it is purchased from Longbai Group Co., Ltd.
[0098] The first anti-settling agent and the second anti-settling agent are both fumed silica, and the fumed silica is purchased from Hubei Huifu Nanomaterial Co., Ltd.
[0099] The curing agent is a modified polythiol curing agent and a modified amine epoxy curing agent.
[0100] The mass ratio of the modified polythiol curing agent to the modified amine epoxy curing agent is 38:16.
[0101] The modified polythiol curing agent was purchased from Guangzhou Green New Materials Co., Ltd., with the brand name of polythiol 309.
[0102] The modified amine epoxy curing agent was purchased from Rich Chemical (Hubei) Co., Ltd. with the brand name R-2028.
[0103] The epoxy accelerator is a phenol epoxy accelerator purchased from Shanghai Qiguang Industry and Trade Co., Ltd. with a brand name of DMP-30.
[0104] The foaming promoter is urea, which was purchased from Jinan Qicai Chemical Co., Ltd.
[0105] The pigment filler is an organic color paste purchased from Guangzhou Panyu Kedi Color Co., Ltd. with a brand number of 4254.
[0106] A second aspect of the present embodiment provides a method for preparing an adhesive for electromagnetic debonding of photovoltaic cutting pads, which comprises at least the following steps: mixing component A and component B respectively and stirring them according to the mass ratio.
[0107] Example 3
[0108] In a first aspect of the present embodiment, there is provided an adhesive for electromagnetic debonding of a photovoltaic cutting pad, wherein the raw materials for preparing the adhesive include:
[0109] Component A: by weight, including 33 parts of modified phenolic epoxy resin F44, 34 parts of bisphenol F epoxy resin 170, 2 parts of a first diluent, 0.1 parts of a dispersant, 0.1 parts of a defoamer, 28.2 parts of a first filler, 4 parts of a foaming agent, 1 part of a first pigment, and 0.6 parts of a first anti-settling agent;
[0110] Component B: by weight, including 51 parts of curing agent, 2 parts of epoxy accelerator, 4 parts of second diluent, 0.3 parts of second pigment, 24.6 parts of second filler, 18 parts of foaming accelerator, and 0.1 parts of second anti-settling agent.
[0111] The mass ratio of the A component to the B component is 1:1.
[0112] The bisphenol F epoxy resin 170 and modified novolac epoxy resin F44 were purchased from Nanya Electronic Materials (Kunshan) Co., Ltd.
[0113] The first diluent is allyl alcohol glycidyl ether, purchased from Shanghai Kaiyin Chemical Co., Ltd.
[0114] The second diluent is benzyl alcohol, purchased from Shanghai Kaiyin Chemical Co., Ltd.
[0115] The dispersant was purchased from BYK Chemicals of Germany with the brand name BYK140.
[0116] The defoamer was purchased from BYK Chemicals of Germany with the brand name BYK016.
[0117] The first filler is magnesium hydroxide, the mesh number of the magnesium hydroxide is 2000 mesh, and it is purchased from Weifang Haililong Magnesium Industry Co., Ltd.
[0118] The second filler is calcium carbonate, the mesh number of the calcium carbonate is 1250 mesh, and it is purchased from Dexing Longsheng Calcium Carbonate Co., Ltd.
[0119] The foaming agent is 4,4'-oxybisbenzenesulfonyl hydrazide, which is purchased from Guangdong Duba New Materials Co., Ltd.
[0120] The pigment is titanium dioxide, the mesh number of the titanium dioxide is 2000 mesh, and it is purchased from Longbai Group Co., Ltd.
[0121] The first anti-settling agent and the second anti-settling agent are both fumed silica, and the fumed silica is purchased from Hubei Huifu Nanomaterial Co., Ltd.
[0122] The curing agent is a modified polythiol curing agent and a modified amine epoxy curing agent.
[0123] The mass ratio of the modified polythiol curing agent to the modified amine epoxy curing agent is 33:18.
[0124] The modified polythiol curing agent was purchased from Guangzhou Green New Materials Co., Ltd., with the brand name of polythiol 309.
[0125] The modified amine epoxy curing agent was purchased from Rich Chemical (Hubei) Co., Ltd. with the brand name R-2028.
[0126] The epoxy accelerator is a phenol epoxy accelerator purchased from Shanghai Qiguang Industry and Trade Co., Ltd. with a brand name of DMP-30.
[0127] The foaming promoter is zinc stearate, purchased from Jinan Qicai Chemical Co., Ltd.
[0128] The pigment filler is an organic color paste purchased from Guangzhou Panyu Kedi Color Co., Ltd. with a brand number of 4254.
[0129] A second aspect of the present embodiment provides a method for preparing an adhesive for electromagnetic debonding of photovoltaic cutting pads, which comprises at least the following steps: mixing component A and component B respectively and stirring them according to the mass ratio.
[0130] Comparative Example 1
[0131] The specific implementation of this comparative example is basically the same as that of Example 1, except that in this comparative example, component A does not contain a foaming agent, but is replaced by an equal amount of 2000 mesh aluminum powder; component B does not contain a foaming promoter, but is replaced by an equal amount of 1250 mesh calcium carbonate.
[0132] Comparative Example 2
[0133] The specific implementation methods of this comparative example are basically the same as those of Example 2, except that the foaming agent of component A in this comparative example is AC foaming agent (Jiangxi Shilong Industrial Co., Ltd.); and component B is the same as that of Example 2.
[0134] Comparative Example 3
[0135] The specific implementation methods of this comparative example are basically the same as those of Example 3, except that in this comparative example, component A does not contain a foaming agent and is replaced by an equal amount of 2000 mesh aluminum powder; component B is the same as that of Example 3.
[0136] Comparative Example 4
[0137] This comparative example uses Example 1 in the Chinese patent "A two-component polyurethane adhesive with high adhesion and rapid degumming by boiling, preparation method and application thereof (patent number: CN202210182872.9)" to prepare the adhesive.
[0138] Comparative Example 5
[0139] This comparative example uses Example 1 of the Chinese patent "Solar crystal rod base plate adhesive, preparation method thereof and solar crystal rod cutting method (patent number: CN 112210331 B)" to prepare the adhesive.
[0140] Performance Testing
[0141] The adhesives prepared in Examples 1-3 and Comparative Examples 1-5 were tested for shear strength, hardness, electromagnetic debonding time and debonding effect. The test results are shown in Table 1.
[0142] The shear strength was tested using the national standard GB / T 7124-2008; the hardness was tested using GB / T531-1999; the electromagnetic debonding used an automatic debonding machine with a power of 23KW and a heating temperature of 100-300°C, and the thickness of the adhesive layer was 0.4-0.6mm. The separation time of the plastic plate and the workpiece plate and the state of the residual film after the plastic plate was separated were recorded.
[0143] Table 1
[0144]
[0145]
Claims
1. An adhesive for electromagnetic debonding of photovoltaic cutting pads, characterized in that: The raw materials for preparing the adhesive include: Component A: by weight, including 40-70 parts of epoxy resin, 2-6 parts of first diluent, 0.1-0.5 parts of dispersant, 0.1-0.5 parts of defoamer, 20-40 parts of first filler, 1-4 parts of foaming agent, 1-3 parts of pigment, and 0.1-0.8 parts of first anti-settling agent; Component B: by weight, including 40-75 parts of curing agent, 1-5 parts of epoxy accelerator, 1-5 parts of second diluent, 0.1-0.3 parts of pigment and filler, 20-50 parts of second filler, 10-20 parts of foaming accelerator, and 0.1-0.3 parts of second anti-settling agent.
2. The adhesive for electromagnetic debonding of photovoltaic cutting pads according to claim 1, characterized in that: The epoxy resin is selected from at least one of bisphenol A epoxy resin, bisphenol F epoxy resin and novolac epoxy resin.
3. The adhesive for electromagnetic debonding of photovoltaic cutting pads according to claim 1, characterized in that: The foaming agent is selected from at least one of a sulfonylhydrazide foaming agent and an amide foaming agent.
4. The adhesive for electromagnetic debonding of photovoltaic cutting pads according to claim 3, characterized in that: The sulfonylhydrazide foaming agent at least includes 4,4'-oxybisbenzenesulfonylhydrazide.
5. The adhesive for electromagnetic debonding of photovoltaic cutting pads according to claim 3, characterized in that: The amide foaming agent at least includes azodicarbonamide.
6. The adhesive for electromagnetic debonding of photovoltaic cutting pads according to claim 1, characterized in that: The curing agent is selected from at least one of a modified polythiol curing agent and a modified amine epoxy curing agent.
7. The adhesive for electromagnetic debonding of photovoltaic cutting pads according to claim 6, characterized in that: The viscosity of the modified polythiol curing agent at 25° C. is 10000-15000 MPa·s.
8. The adhesive for electromagnetic debonding of photovoltaic cutting pads according to claim 6, characterized in that: The modified amine epoxy curing agent is a diethylenetriamine modified amine epoxy curing agent, the viscosity of the modified amine epoxy curing agent at 25° C. is 10000-20000 MPa·s, and the amine value is 200-500 mg KOH / g.
9. The adhesive for electromagnetic debonding of photovoltaic cutting pads according to claim 1, characterized in that: The foaming promoter is selected from at least one of urea and zinc stearate.
10. A method for preparing an adhesive for electromagnetic debonding of photovoltaic cutting pads according to any one of claims 1 to 9, characterized in that: At least the following steps are included: Component A and component B are mixed evenly respectively and then stirred according to the mass ratio to obtain the product.
Citation Information
Patent Citations
Solar cell base plate adhesive, its preparation method and solar cell cutting method
CN112210331B
High-adhesion two-component polyurethane adhesive capable of being quickly degummed after being boiled in water as well as preparation method and application of high-adhesion two-component polyurethane adhesive
CN114605954A
A two-component epoxy adhesive, its preparation method and application
CN115353847B